Patterns of baby language in Bwe Karen - Henderson, Eugénie J. A. (2024)
Scattered amongst my Bwe Karen material collected many years ago are a number of expressions described by my informant as 'baby language'. Material of this kind often escapes attention in formal grammars and dictionaries, and may at first sight seem to offer little of value to philologists, and yet it is not unknown for such linguistic by-paths to conserve forms that have disappeared elsewhere.